2017
DOI: 10.1186/s13063-017-2006-4
|View full text |Cite
|
Sign up to set email alerts
|

COgnitive behavioural therapy versus standardised medical care for adults with Dissociative non-Epileptic Seizures (CODES): statistical and economic analysis plan for a randomised controlled trial

Abstract: BackgroundDissociative seizures (DSs), also called psychogenic non-epileptic seizures, are a distressing and disabling problem for many patients in neurological settings with high and often unnecessary economic costs. The COgnitive behavioural therapy versus standardised medical care for adults with Dissociative non-Epileptic Seizures (CODES) trial is an evaluation of a specifically tailored psychological intervention with the aims of reducing seizure frequency and severity and improving psychological well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…More women than men were interviewed to reflect the higher prevalence of DS among women in the CODES study [ 22 ] and the population with DS more widely. The majority (20/22) of participants randomized to receive CBT who were interviewed here attended at least nine CBT sessions and were therefore classified as compliant with the DS-specific CBT in the study [ 23 ]. Those interviewees allocated to CBT + SMC attended a median of 3.5 SMC sessions (range: 0–10 sessions), while those patients allocated to SMC-alone attended a median of 4 SMC sessions (range: 2–6 sessions).…”
Section: Resultsmentioning
confidence: 99%
“…More women than men were interviewed to reflect the higher prevalence of DS among women in the CODES study [ 22 ] and the population with DS more widely. The majority (20/22) of participants randomized to receive CBT who were interviewed here attended at least nine CBT sessions and were therefore classified as compliant with the DS-specific CBT in the study [ 23 ]. Those interviewees allocated to CBT + SMC attended a median of 3.5 SMC sessions (range: 0–10 sessions), while those patients allocated to SMC-alone attended a median of 4 SMC sessions (range: 2–6 sessions).…”
Section: Resultsmentioning
confidence: 99%
“…Determining the long-term outcome of PNES across borders and cultures has important clinical implications. For example, a recent well-designed clinical trial on 38 patients [6], with relatively a short follow up period (16 weeks), showed that the best current practice (combined CBT with sertraline) resulted in 59.3% seizure reduction which was significantly better compared with that in the treatment as usual group. A recent metaanalysis synthesized data from 13 studies with a total of 228 patients with PNES [15]; results showed that 47% of the patients with PNES were seizure-free upon completion of a psychological intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, access to resources are limited in Iran and many other developing countries compared to that in the Western countries. Current best practice in the management of patients with PNES includes combined psychotherapy (e.g., cognitive behavioral therapy) and treatment of any psychiatric comorbidities [6]. In spite of that, access to appropriate psychotherapy is limited in many places in Iran (see the methods).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-randomisation measure of DS frequency was DS occurrence over the 4 weeks prior to psychiatric assessment (Robinson et al, 2017) with subjective severity of DS, and how Goldstein et al (2019). In addition, variables predicting which of the 698 participants did not attend psychiatry appointments have been reported by Stone et al (2020).…”
Section: Ds Occurrencementioning
confidence: 99%